2012
DOI: 10.4103/0970-1591.98457
|View full text |Cite
|
Sign up to set email alerts
|

Virtual cystoscopy (pneumo-cystoscopy)-Its utility in the prospective evaluation of bladder tumor

Abstract: Aim:To evaluate the role of virtual cystoscopy (VC) comparing it with cystopanendoscopy (CPE) for detecting bladder tumor(s).Material and Methods:Ethical clearance was obtained from the Institutional ethics committee. After an informed consent 30 patients fulfilling the inclusion criteria were enrolled in the prospective non-randomized clinical study and were evaluated as per protocol with VC performed by a qualified radiologist who was blinded to the findings of CPE performed by a qualified urologist. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Urinary bladder may be an ideal intra-abdominal organ for virtual endoscopic navigation because of its simple luminal morphology, its small volume and the absence of peristalsis [4]. In this study, we tried to assess the utility of virtual cystoscopy in diagnosis of new and recurrent bladder tumors compared to conventional cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary bladder may be an ideal intra-abdominal organ for virtual endoscopic navigation because of its simple luminal morphology, its small volume and the absence of peristalsis [4]. In this study, we tried to assess the utility of virtual cystoscopy in diagnosis of new and recurrent bladder tumors compared to conventional cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion. It is suggested that urinary bladder may be an ideal intraabdominal organ for virtual endoscopic examination because of its simple luminal morphology, small volume and the absence of peristalsis [ 4 ]. Assisted virtual Fig.…”
mentioning
confidence: 99%